The value of MRI for differentiating benign from malignant sex cord-stromal tumors of the ovary: emphasis on diffusion-weighted MR imaging - Shu-Hui Zhao; Hai-Ming Li; Jin-Wei Qiang; Deng-Bin Wang; Hua Fan (BMC, 2018)
Abstract Background To investigate MRI for differentiating benign from malignant sex cord-stromal tumors of the ovary (SCSTs) emphasizing on the value of diffusion-weighted (DW) magnetic resonance (MR) imaging. Methods This retrospective study included 29 benign SCSTs in 28 patients and 13 malignant SCSTs in 13 patients. DW imaging as well as conventional MR imaging was performed. Signal intensity on DW imaging was assessed and apparent diffusion coefficient (ADC) value was measured. In addition, T2 signal intensity and contrast enhancement pattern were also assessed and compared between benign and malignant SCSTs. Results Both of the T2 hypointensity and mild enhancement were specific to benign SCSTs. The majority of malignant SCSTs showed high signal intensity on DW imaging, whereas most benign SCSTs showed low or moderate signal intensity (p = 0.000). Fibromas were the tumors with the lowest observed ADC value (0.470 × 10− 3 mm2/s). Sclerosing stromal tumors were the tumors with the highest observed ADC value (2.291 × 10− 3 mm2/s). ADC value of solid component was significantly lower in malignant SCSTs (0.825 ± 0.129 × 10− 3 mm2/s) than in benign SCSTs (1.343 ± 0.528 × 10− 3 mm2/s) when fibromas were excluded (p = 0.024). T2, DCE and DW imaging has a limited value on the differential diagnosis of the benign and malignant SCSTs with an accuracy of 69.0%,71.4% and 78.1% respectively. Combination of T2, DCE and DW imaging permitted the distinction with an accuracy of 88.0%. Conclusions It is more helpful for distinction of the benign and malignant SCSTs by combining of T2, DCE and DW imaging than using each of the three sequences independently.